Literature Review 2020-2025: Innovation of Pop-Up Book Employing Problem Based Learning to Improve Students’ Learning Outcomes and Critical Thinking Skills - Winda Kumalasari; Sri Haryani; Arif Widiyatmoko; Bambang Subali (Journal of Educational Sciences, 2026)
The rapid development of digital learning media necessitates that educators implement engaging and effective instructional strategies. One innovative tool gaining significant attention is the pop-up book. This study aims to evaluate the enhancement of students’ learning outcomes and critical thinking skills through the integration of pop-up books within a Problem Based Learning (PBL) approach. The research methodology employed is a Systematic Literature Review (SLR) covering publications from 2020 to 2025. A total of 500 articles indexed in Google Scholar were analyzed using bibliometric mapping via Publish or Perish and VOSviewer, with twenty five key articles selected for in-depth examination. The findings indicate that contemporary research focuses heavily on the synergy between interactive learning media and instructional models, with the combination of pop-up books and PBL emerging as a frequently explored variable. Evidence suggests that employing pop-up books within a PBL framework effectively improves both academic performance and critical thinking abilities. Consequently, this integration serves as a practical and innovative teaching strategy to meet the demands of modern education.